IMPROVING THE EFFICIENCY OF INFORMATION SECURITY IN THE CONSTRUCTION AND OPERATION OF VARIOUS CONTROL SYSTEMS (American Journal of Technology and Applied Sciences, 2024)
In this article, the increase in the number and types of cybercrimes occurring in the world as a result of the development of the Internet has a significant impact on big data, the issue of storing large amounts of data and ensuring security in communication channels is focused on. In this process, proposals are made to ensure the security of big data and prevent its loss. In particular, in the construction of any intellectual system of information security management, it is envisaged to take into account the total costs and losses of the object receiving the information.